Pengaruh Video Pembelajaran Animasi terhadap Kemampuan Menulis Narasi Siswa Kelas IV Bator 1 Klampis - Iffatul Qutsiyah; Ibnu Ansori; Ika Dian Rahmawati; Apot Nunukwau (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research is motivated by the low narrative writing ability of fourth-grade elementary school students, characterized by students' difficulties in developing ideas, organizing storylines, choosing appropriate vocabulary, and writing coherently. One effort that can be made to address this problem is to utilize animated learning videos as instructional media. This study aims to determine the effect of animated learning videos on the narrative writing ability of fourth-grade elementary school students. The research employed a quantitative approach with a Pre-Experimental Design method and a One Group Pretest-Posttest Design. The research subjects consisted of 25 fourth-grade students. Data collection techniques were carried out through tests and observation. Data analysis used descriptive statistics, normality tests, N-Gain calculations, and paired sample t-tests. The results showed that the students' average pretest score of 58.64 increased to 76.28 in the posttest. The percentage of learning mastery increased from 28% to 80%. The N-Gain calculation result of 0.43 was categorized as moderate. In addition, the hypothesis test results showed that the calculated t-value of 9.87 was greater than the t-table value of 2.06 at a significance level of 0.05, so H0 was rejected and H1 was accepted. Thus, it can be concluded that animated learning videos have a significant effect on the narrative writing ability of fourth-grade elementary school students. This media can be used as an effective learning alternative to improve students' narrative writing skills.